Cigarette smoking quit ratios among adults in the USA with cannabis use and cannabis use disorders, 2002–2016. Issue 1 (5th April 2019) - Weinberger, Andrea H; Pacek, Lauren R; Wall, Melanie M; Gbedemah, Misato; Lee, Joun; Goodwin, Renee D
Abstract : Background: The prevalence of cigarette smoking is nearly three times higher among persons who use cannabis and have cannabis use disorders (CUDs), relative to those who do not. The current study examined cigarette quit ratios from 2002 to 2016 among US adults with and without cannabis use and CUDs. Methods: The current study analysed US adults aged 18 years and older from the National Survey on Drug Use and Health, an annual cross-sectional study. Quit ratios (ie, proportion of former smokers among ever-smokers) were calculated annually from 2002 to 2016. Time trends in quit ratios by cannabis use/CUDs were tested using logistic regression. Results: In 2016, the quit ratios for people with any cannabis use (23%) and CUDs (15%) were less than half the quit ratios of those without cannabis use and CUDs (51% and 48%, respectively). After controlling for demographics and substance use disorders, the quit ratio did not change from 2002 to 2016 among persons with CUD, though it non-linearly increased among persons with cannabis use, without cannabis use and without CUDs. Quit ratios increased more rapidly among those who reported past-month cannabis use compared with those without past-month cannabis use. Conclusions: Cigarette smoking quit ratios remain dramatically lower among people who use cannabis and have CUDs and quit ratios did not change significantly from 2002 to 2016 among those with CUDs. Public health and clinical attention are needed to increase quit ratios and reduce harmful cigarette smoking consequences for persons with cannabis use and CUDs.